DAMPAK KEBIJAKAN OPERATION SOVEREIGN BORDERS TERHADAP PENCARI SUAKA YANG AKAN MASUK KE AUSTRALIA - Wahyu Rahmatullah; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Australia is one of the popular destinations for refugees and asylum seekers compared to countries in Europe. The increase in the number of refugees and voters to Australia saw a significant increase in the year resulting in Australia under the government of Prime Minister (PM) Tony Abbot, issuing the Operation Sovereign Borders policy. This policy has come under fire from the international community and has a profound effect on Australia and countries that have direct contact with refugees and asylum seekers. This research uses securitization theory with a level of state analysis. Securitization is a theory developed by thinkers from the Copenhagen School including Barry Buzan, Ole Weaver and Jaap de Wilde. According to the Copenhagen School, the Securitization Process has two stages, including the stage of raising issues and the stage of convincing the audience. The qualitative method in this study uses secondary data studied with document analysis techniques. This research shows that the OSB policy during PM Abbott's reign can indeed be said to have succeeded in reducing the arrival of boat people. But on the other hand, the implementation of such policies has the potential to violate human rights through non-observance of the principle of non-refoulement. In reality, asylum-seeking boats that came to Australia during PM Abbott's reign have been blocked and returned to their home territories. Their return to the region of origin is a violation of the principle of non-refoulement that has been recognized as customary international law. Australia is a popular destination for refugees and asylum seekers compared to countries in Europe, as the European region has adopted stricter refugee policies. Keywords: Australia, Asylum Seekers, Operation Sovereign Borders Policy, Schengen Convention, Dublin Convention.